Clinicoradiological and demographic pattern in diffuse parenchymal lung diseases: An observational study - Yadav, Harendra; Srivastava, Rahul (International Journal of Medical Research and Review, 2018)
Introduction: Diffuse parenchymal disease is a group of lung disease affecting alveolar epithelium, pulmonary capillary endothelium, basement membrane, perivascular and perilymphatic tissue. It includes many diseases like IPF, Sarcoidosis, BOOP, COP, LAM etc. it is still under diagnosed entirety. Many patients die due to lack of awareness and investigating modalities. Aims and objective: This study is to see Demographic pattern of DPLD, its clinical pattern and radiological findings in different type of ILDs. Study Type: It is a Prospective Observational Study done over a period of 1 year. Material & Method: Patients studied over20 years of age and having respiratory symptoms. We excluded patients of other diseases like COPD, Tuberculosis etc. Total 75 patients were diagnosed as a case of DPLD by clinical findings, and investigations like X ray chest, HRCT thorax, Bronchoscopy. Results: Most common ILD (Interstitial lung Disease) is IPF 40.0% followed by Sarcoidosis etc. Most common clinical symptom was breathlessness (100.00%) in IPF, Fever & Chest Pain are common in Granulomatous type. Conclusion: DPLD (Diffuse Paranchymal lung Disease) is a chronic lung disease characterized by progressive decline in lung function. IPF is most common in DPLD and leads to fast deterioration of lung function. HRCT (High Resolution computed tomography) is very important to assess type of disease. Spirometry, Broncoscopy are important for diagnosis of ILD and lung function.